Coping with anxiety, depression, anger and aggression : the mediational role of resilience in adolescents. - Ng, Reuben. (2008)
The purpose of this study was to test a mediational model of resilience on adolescents undergoing normative development. Specifically, the study tested the mediating role of resilience (consisting of positive thinking, tenacity and help seeking) in the coping—psychopathology relationship. The latter included internalizing conditions (anxiety and depression) and externalizing behaviors (anger and aggression). To actualize these goals, 719 adolescents from two government-aided secondary schools in Singapore were recruited to fill up surveys measuring coping, resilience, anxiety, depression, anger and aggression. Mediation analysis using Structural Equation Modeling (SEM) elucidated that resilient factors mediated the approach coping-psychopathology link but not the avoidance coping-psychopathology link. Specifically, positive thinking mediated the approach coping- internalizing conditions (anxiety and depression) link; tenacity mediated the approach coping-externalizing behaviors (aggression) link; help seeking mediated both the approach coping-internalizing condition (anxiety and depression), and approach coping-externalizing behaviors (anger and aggression) links. Further, strength-of-mediation analysis—conducted for links with two or more mediators—revealed that help seeking was a stronger mediator than positive thinking in the approach coping-anxiety relationship. In the other relationships (approach coping - depression, aggression), respective mediators were equally strong. These findings hope to provide a theoretical basis on which future resilience intervention programs can be designed—highlighting especially the importance of approach coping, positive thinking, tenacity and help seeking for Asian adolescents.